Gas gun ramp loading of Kel-F 81 targets using a ceramic graded areal density flyer system. (June 2015) - Goff, M.; Hazell, P.J.; Appleby-Thomas, G.J.; Wood, D.C.; Stennett, C.; Taylor, P.
Abstract: Kel-F 81 (PCTFE/Polychlorotrifluoroethylene) polymer targets were subjected to ramp loadings generated by a ceramic flyer accelerated into the targets by a gas gun in the plate impact configuration. This approach used a ceramic graded areal density flyer in conjunction with a ceramic buffer plate to induce a ramp loading in the target. The flyer was comprised of a rapid prototyped alumina ceramic. The loading was observed with embedded electromagnetic particle velocity gauges (PV gauges) with the results compared with ANSYS Autodyn™ hydrocode simulations. Experimental results show that ramp loadings of varying duration and magnitude were induced into the target. These loadings can be described as shockless compressions leading to shocked states within the material. In addition, numerical simulations provided further insight into the loading approach – with good agreement found with experimental data, opening the potential to design more complex loading systems in future. Highlights: A novel graded areal density ramp loading method was developed. This ceramic material method is compatible with embedded particle velocity gauges. Flyers are constructed using ceramic stereolithography. Quasi one-dimensional loadings have been observed in Kel-F targets. Autodyn simulations have reproduced key features of experimental results.